Studi Komparasi Efektifitas Penerapan Model Pembelajaran Pjbl Sebelum Dan Sesudah Pandemi - Wahyu Fatihah (Prosiding Temu Ilmiah Nasional Guru, 2022)
Project Based Learning (PjBL) is one of the student-centered learning models. The purpose of the study was to compare the effectiveness of using PjBL learning models before the pandemic, during the pandemic and after the pandemic in overcoming learning loss. The research design used the One Group Pretest-Posttest design model, with the research subjects being students of class XII IPA 1 to XII IPA 3 at SMAN 4 Cilegon. The presentation of the data uses a qualitative description that combines observational data, the percentage of learning completeness results and the interpretation of the N-gain value. The results of data processing resulted in the percentage of students' learning mastery before the pandemic was 80.3%, during the pandemic it fell very significantly to 23.5% and after the pandemic it rose again although it was not yet significant to 40.2%. The N-gain results show that before the pandemic it was 67% (quite effective), during the pandemic it fell very significantly to 4% (ineffective) and after the pandemic it rose again even though it was not significant to 51% (less effective). This shows the effect of learning loss due to online learning during the pandemic.